Next-generation re-sequencing as a tool for rapid bioinformatic screening of presence and absence of genes and accessory chromosomes across isolates of Zymoseptoria tritici. - McDonald, M.; Williams, A.; Milgate, A.; Pattemore, J.; Solomon, P.; Hane, James (Academic Press, 2015)
The wheat pathogen Zymoseptoria tritici possesses a large number of accessory chromosomes that may be present or absent in its genome. The genome of the reference isolate IPO323 has been assembled to a very high standard and contains 21 full length chromosome sequences, 8 of which represent accessory chromosomes. The IPO323 reference, when combined with low-cost next-generation sequencing and bioinformatics, can be used as a powerful tool to assess the presence or absence of accessory chromosomes. We present an outline of a range of bioinformatics techniques that can be applied to the analysis of presence–absence variation among accessory chromosomes across 13 novel isolates of Z. tritici.